If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1(x + -1) = -4x + 39 Reorder the terms: 1(-1 + x) = -4x + 39 (-1 * 1 + x * 1) = -4x + 39 (-1 + 1x) = -4x + 39 Reorder the terms: -1 + 1x = 39 + -4x Solving -1 + 1x = 39 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -1 + 1x + 4x = 39 + -4x + 4x Combine like terms: 1x + 4x = 5x -1 + 5x = 39 + -4x + 4x Combine like terms: -4x + 4x = 0 -1 + 5x = 39 + 0 -1 + 5x = 39 Add '1' to each side of the equation. -1 + 1 + 5x = 39 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 39 + 1 5x = 39 + 1 Combine like terms: 39 + 1 = 40 5x = 40 Divide each side by '5'. x = 8 Simplifying x = 8
| 8+3p=9 | | -3x^2+6x+5= | | 4(8-5p)-6=26 | | 1/9-2/3b=1/18 | | m-2/3m19x2m+6/2m-4 | | 5-7m=-6m+1 | | (1/5)(2x+5)=8x | | log(5)5=1 | | -3(t+5)(4t+2)=8 | | 4(x-3)=2x+0 | | 3(c-1)= | | x+2(x-4)= | | 5(x+6)=2(x+9) | | x^2+7x=9x+3 | | 2k-3/-5=7 | | log(2)32=5 | | -2/2k=7 | | 3x+4y=925 | | 7(-2)+10=2(-7) | | -60.2=5/9f | | 4x+3x=9.25 | | 1/x^2-2 | | 49s^2-100=0 | | 4g-9g+3=-32 | | log(7)1=0 | | -2x+10=x+3 | | 2/3k-4=-6 | | 9x-4(x-2)=17+13x-7-8x | | y=-x^4-6x^3+6x^2-6x+5 | | -2a-11-3a=14 | | (2x+12)=3/4x+27 | | 3(z-2)+6=5(z+4)solve |